Tuning the biomimetic behavior of hybrid scaffolds for bone tissue engineering through surface modifications and drug immobilization - Ghorbani, Farnaz; Ghalandari, Behafarid; Sahranavard, Melika; Zamanian, Ali; Collins, Maurice N. (Materials Science and Engineering C, 2021)
Bone defects arising from injury and/or disease are a common and debilitating clinical lesion. While the development of tissue microenvironments utilizing biomimetic constructs is an emerging approach for bone tissue engineering. In this context, bioactive glass nanoparticles (BGNPs) were embedded within polycaprolactone (PCL) scaffolds. The scaffolds exhibit an engineered unidirectional pore structure which are surface activated via oxygen plasma to allow immobilization of simvastatin (SIM) on the pore surface. Microscopic observation indicated the surface modification did not disturb the lamellar orientation of the pores improving the biomimetic formation of hydroxyapatite. Mathematically modelled release profiles reveal that the oxygen plasma pre-treatment can be utilized to modulate the release profile of SIM from the scaffolds. With the release mechanism controlled by the balance between the diffusion and erosion mechanisms. Computational modelling shows that Human Serum Albumin and Human alpha 2-macroglobulin can be utilized to increase SIM bioavailability for cells via a molecular docking mechanism. Cellular studies show positive MG-63 cell attachment and viability on optimized scaffolds with alkaline phosphatase activity enhanced along with enhanced expression of osteocalcoin biomarker.
CRIS-Team WoS Importer:2021-10-15